The Influence of a Concrete Media-Assisted Guided Discovery Learning Model on Students' Learning Interests and Creative Thinking Abilities in Science Learning at Cluster VI, Sutera District - Ratna Nengsih; Ismira Ismira; Alfroki Martha (Journal of Educational Sciences, 2026)
This study addresses the low learning interest and limited creative thinking skills of fifth-grade students in science classes at Gugus VI, Sutera Subdistrict. These issues are associated with the lack of varied learning media, minimal student participation, and the dominance of teacher-centered instruction. The research aimed to determine the effect of the Guided Discovery Learning model supported by concrete media on students’ learning interest and creative thinking abilities. A quasi-experimental design was used, specifically the posttest-only control group design. The population consisted of all fifth-grade students in Gugus VI, with SDN 25 Amping Parak as the experimental group and SDN 29 Teratak Panas as the control group. Data were collected through a learning interest questionnaire and a creative thinking test containing statements and essay questions. The data were analyzed using the Mann-Whitney U test in SPSS 27. The results showed a significant difference between students taught using Guided Discovery Learning with concrete media and those taught conventionally. The significance values of the questionnaire (0.001 < 0.05) and the test (0.000 < 0.05) indicated that the model effectively increased learning interest and creative thinking skills.